2022
DOI: 10.3349/ymj.2022.63.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Changes in Adjacent and Index Levels after Cervical Disc Arthroplasty

Abstract: Purpose The purpose of this retrospective study was to evaluate radiological and clinical outcomes in patients undergoing cervical disc arthroplasty (CDA) for cervical degenerative disc disease. The results may assist in surgical decision-making and enable more effective and safer implementation of cervical arthroplasty. Materials and Methods A total of 125 patients who were treated with CDA between 2006 and 2019 were assessed. Radiological measurements and clinical out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…These findings have been replicated in clinical studies with significantly less ROM at adjacent levels in hybrid constructs than in multilevel ACDF [113]. Following CDA, index-level ROM improves and is maintained at long-term follow-up [94,97,103,104,106,108,[114][115][116][117]. This preservation of native ROM at the index and adjacent levels may reduce future ASD development.…”
Section: Motion Preservation 71 Cervical Disc Arthroplastymentioning
confidence: 66%
See 1 more Smart Citation
“…These findings have been replicated in clinical studies with significantly less ROM at adjacent levels in hybrid constructs than in multilevel ACDF [113]. Following CDA, index-level ROM improves and is maintained at long-term follow-up [94,97,103,104,106,108,[114][115][116][117]. This preservation of native ROM at the index and adjacent levels may reduce future ASD development.…”
Section: Motion Preservation 71 Cervical Disc Arthroplastymentioning
confidence: 66%
“…Similarly, dysphagia following single-level CDA was demonstrated to occur at lower rates compared to ACDF at 7-year follow-up [124]. HO formation following CDA is a known potential outcome, with variable incidence rates in the literature ranging from 0% to 75% [100,108,115,125]. Its clinical significance has yet to be established [126].…”
Section: Motion Preservation 71 Cervical Disc Arthroplastymentioning
confidence: 99%
“…The patient cohort examined in the current study demonstrated significant improvements in all clinical outcome parameters (NDI, VAS, and JOA) in comparison to baseline levels. Previous studies have also verified similar favorable clinical outcomes at different observation periods, irrespective of the type of prosthesis implanted [19][20][21][22]. It has been suggested that higher pre-operative NDI scores are associated with a more pronounced C2-C7 sagittal vertical axis and reduced cervical lordosis [23].…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, plain radiographic assessment remains the front-line patient assessment tool for cTDR [ 12 , 16 ]. Previous studies have underscored the need for classification of radiographic changes around cTDR including heterotopic ossification (HO) [ 17 , 18 ] and bone loss [ 12 , 19 ].…”
Section: Introductionmentioning
confidence: 99%